Menggali Tradisi Takir Plontang: Warisan Budaya Jawa di Desa Tebing Kaning, Kecamatan Arma Jaya, Kabupaten Bengkulu Utara - Biomed, Marisadonna Asteria M.; Kesuma, Erwin; Santaria, Santaria; Ramdani, Syahrul Oktarian; Wardi, Ahmad Suhro; Gutama, Mebryando; Simbolon, Cinthya Claudia; Arsih, Chairunnisa Della; Afsyah, Aulia Nurul; Simanullang, Yulia Oktaviani; Meiriska, Dwita; Igamario, Sultan Syarief; Toar, Andro Yesaya; Hutasoit, Marta Kristina; Ramadanil, Nofri; Pujiana, Ajeng (Abdimas Indonesian Journal, 2024)
The Takir Plontang tradition is a cultural heritage of the Javanese people who celebrate the month of Muharram in Tebing Kaning Village, North Bengkulu. The month of Muharram, as the first month. In the Hijriyah calendar, it has various features in Islamic teachings, and the Javanese people in this village interpret it through making Takir Plontang. Takir Plontang is a rectangular banana leaf container used to serve rice and side dishes. This tradition not only has spiritual value, but also strengthens social relations among village residents, reminds them of the importance of being grateful for the blessings they have received, and strengthens ties of friendship. This research aims to identify and document the implementation of the Takir Plontang tradition in Tebing Kaning Village, examine the social and economic impacts of this tradition, and explore the potential for developing Takir Plontang as a cultural tourism attraction. The research method used is qualitative with a descriptive approach, involving observation, interviews and literature study. The research results show that the Takir Plontang tradition has a significant social impact, strengthening ties and increasing the sense of solidarity among village residents. Apart from that, this tradition also has great potential to be developed as a cultural tourism attraction. It is hoped that this research can contribute to efforts to preserve cultural heritage and develop culture-based tourism in Tebing Kaning Village. Recommendations for the preservation and development of Takir Plontang include increasing documentation and research, education and training, government support, as well as promotion through social media and the official website.